REINTERPRETASI DAN REFORMULASI MAKNA JIHAD DAN QITAL (Studi Historis Islam dalam Tafsir Tematik) - Suhaimi Suhaimi (STIU Al-Mujtama Pamekasan, 2017)
Akhir-akhir ini makna antara jihad dan qital semakin terasa kabur, bahkan terkesan dianggap sebagai landasan aksi terorisme, dianggap sebagai sinonim kata. Banyak terjadi kekerasan atas nama agama dengan mengusung tema jihad. Untuk menemukan konsep yang sebenarnya perlu melakukan reinterpretasi dan reformulasi terhadap ketentuan jihad Islam dengan menelaah sosio-historisnya dalam tafsir tematik. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi pustaka (library research) It is known commonly that the term jihad is sometimes misunderstood and misused bay both Moslems and no-Moslems that causes Islam become scapegoat when the act of terrorism occurs. This paper will elaborate on around this issue. By using qualitative approach, the analysis has brought about two important results. These are, the first: the term jihad in al-Qur’an cannot be interpreted just synonymous with the term qital, and the term qital is better understood as one of the forms and techniques of jihad; and second: from Tafsir analysis of some verses on qital understood that the spread of Islam, using the jihad was done with some steps in two period, that are, the period of Mecca and the period of Medina